The School for Good and Evil - Chainani, Soman; Bruno, Iacopo (New York, NY : Harper, 2013)
Best friends Sophie and Agatha discover their true identities when they enter The School for Good and Evil, a school where ordinary boys and girls are trained to be fairy tale heroes and villains.
School Library Journal, June 2013
Booklist, May 2013
Bulletin (Center for Children's books), June 2013
Publishers Weekly Annex, June 2013
5.2
5-8
Keywords: Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Good and evil -- Juvenile fiction; Friendship -- Fiction; Schools -- Fiction; Good and evil -- Fiction; Fantasy; Friendship -- Fiction; School stories; Good and evil -- Fiction; Fantasy fiction; Fantasy fiction